Jonathan K. Gosnell. Franco-America in the Making: The Creole Nation Within. U of Nebraska P, 2018. - Anna V Keefe (Studies in 20th & 21st Century Literature, 2020)
Review of Jonathan K. Gosnell. Franco-America in the Making: The Creole Nation Within. U of Nebraska P, 2018. 347 pp.
Keywords: Franco-America; creole; francophone; postcolonial